Strategi Komunikasi Pemasaran Dalam Meningkatkan Penjualan Barang Dan Jasa Bengkel Mobil Istana Motor (Studi Kasus Bengkel Mobil Istana Motor) - Pristiana, Meysa; Ichsan, Muhammad; Nurdiansyah, Chepi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
With the increasing number of car repair shops opening, the higher the sales competition for the Istana repair shop company, they both sell the same products and offer the same services, so a proper marketing communication plan is needed to continue to increase the Company's sales. Istana Workshop has been established since 2013 and continues to grow following the development of four-wheeled vehicles to date. This study uses a qualitative research method with a descriptive approach, which aims to provide a more comprehensive and more detailed description of the research object based on the facts that occur and the phenomena studied. The data collected in this study are not presented in the form of numbers, but in the form of narrative descriptions from interviews, observations, personal documents, and other documents that can be used as supporting evidence. Istana Motor Workshop is a company engaged in the sale of goods and services for four-wheeled vehicles. The research conducted by the researcher is about the marketing communication strategy in increasing sales of goods and services of the Istana Motor car repair shop, resulting in several conclusions. One of them is that this company increases sales of goods and services with a word of mouth strategy because our company takes advantage of spreading relations to increase sales.